ANALISIS RISIKO PADA PROYEK PEMBANGUNAN GEDUNG LABORATORIUM TERPADU PENDUKUNG BLOK MASELA UNIVERSITAS PATTIMURA - Nurhayati Maasily; Octovianus Jamlaay; Nelda Maelissa (Jurusan Teknik Sipil, 2023)
Risk management is an effort to manage risk in a comprehensive, planned and structured manner in a good system to prevent unexpected events. It allows management to improve results by identifying and analyzing the risk of work accidents that exist, namely the construction project of Masela Block Supporting Integrated Laboratory, Pattimura University. Each risk of the work phase must be assessed for professional risk management/control. The assessment method applied a risk assessment matrix sourced from NHS Highland which was adopted from AS/NZS 1360:2004 Risk Management. The secondary data obtained for this study consists of the company's organizational structure and project work items. Primary data obtained from observations in the field that is obtained by conducting interviews and distributing questionnaires. The data analysis carried out in this study was a variable test, namely Validity Test and Reliability Test. The next step was the application of risk assessment. The result of this study was that there were 4 risk factors, namely human resources, equipment and work materials, work methods, and working environment. The classification of the risk level from the 29 variables of occupational accident risk, there were two work risks that were included in the high-risk category and the other 27 risks were included in the medium risk category. Based on known risks, a strategy that can be carried out is obtained, namely risk control based on the classification of risk levels, namely Elimination, Substitution, Administration, and Personal Protective Equipment.